Gestión administrativa de la empresa “Corte Global Energy” periodo 2022 - Castro Mero, Katiuska Katherine (2023)
This study focuses on the administrative management of the company "Corte Global Energy" during the year 2022, a prominent company in the energy sector known for its focus on innovation and operational excellence. The primary objective of this research is to conduct a detailed analysis of the decision-making process within the organization in order to identify deficiencies and comprehend their impact on overall performance. Challenges were faced in the decision-making process, the underutilization of human talent, and the lack of optimization of available resources during the year 2022. This research utilizes a descriptive and analytical approach, along with exploratory and applied research methods. Information was gathered through interviews and questionnaires directed at the personnel of "Corte Global Energy" involved in decision-making and human resources management during that period. Administrative management is crucial for the efficient operation of any company, and this research aims to enhance the understanding of how management affects financial performance and profitability. The proposal advocates for the application of more advanced administrative concepts to optimize human resources and improve productivity. It is observed that the lack of knowledge in management and the analysis of time and motion have led to inefficiencies in the company's operational processes. It is essential to apply a more scientific approach to administrative management to achieve efficiency and effectiveness in goal attainment. The importance of updating administrative procedures is highlighted, with a focus on elements such as service waiting times, staff courtesy, and corporate image. The need for continuous training for operational personnel is also emphasized.